2008
DOI: 10.1007/s11695-008-9753-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stoma Size on Weight Loss After Laparoscopic Gastric Bypass Surgery: Results of a Blinded Randomized Controlled Trial

Abstract: The level of restriction or the presence of stenosis achieved by different circular stapler sizes does not have a significant causative role in weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 10 publications
(11 reference statements)
3
24
2
Order By: Relevance
“…Gould et al [23] found a significantly reduced incidence of anastomotic strictures using the 25-mm circular stapler compared to the 21-mm circular stapler, but no negative influence of the wider anastomosis on the EWL at 1 year. Both results correlate to the findings of Nguyen et al [24] and Cottam et al [25].…”
Section: Discussionsupporting
confidence: 92%
“…Gould et al [23] found a significantly reduced incidence of anastomotic strictures using the 25-mm circular stapler compared to the 21-mm circular stapler, but no negative influence of the wider anastomosis on the EWL at 1 year. Both results correlate to the findings of Nguyen et al [24] and Cottam et al [25].…”
Section: Discussionsupporting
confidence: 92%
“…In 2009 we also found that the only significant effectors of weight loss at one year were gender and BMI (26). This study correlates directly with our results that other factors are not significant in predicting excess weight loss at one year.…”
Section: Discussionsupporting
confidence: 85%
“…Literature is also split of whether age effects weight loss however we did not find it to be significant (7,23 paper (26) and this one as well.…”
Section: Discussionmentioning
confidence: 58%
“…The importance of the size of the gastric pouch and the gastrojejunostomy, for long-term weight loss, has been debated since the very start of bariatric surgery. Stoma size has been shown in several studies to be of importance for gastroplasties [15,16], but not for RYGB [17,18]. The first pouches in gastric bypass had a volume of about 200 ml, according to the inventor Dr Mason [19], and were vertically orientated, containing a large part of the greater curvature, prompt for later dilatation.…”
Section: Discussionmentioning
confidence: 99%